How to monetize your data - Wixom, Barbara Haley 1969-; Ross, Jeanne W. (MIT Sloan Management Review, 2017)
Companies can monetize their data by improving internal business processes and decisions, wrapping information around core products and services, and selling information offerings to new and existing markets. Adopting any of these approaches, however, requires management commitment to specific organizational changes and targeted technology and data management upgrades.